Avaliação dos níveis de cortisol em saliva artificial por espectrometria de massas - (:unkn) unknown (Universidade Brasil, 2020)
Measurement of the level of cortisol in biological fluids is used in some diagnoses. Currently, one of the most used analytical techniques to measure its levels is mass spectrometry (MS), with wide application in the most varied areas of science. The objective of this study was to propose a method of rapid analysis, without sample preparation, to assess the level of cortisol in a saliva sample using the mass spectrometry technique by paper spray ionization and multivariate analysis. Thus, mass spectra in the region of 100-800 m / z were acquired with a Thermo Fisher Scientific LCQ FLEET model equipped with a low-resolution Ion Trap mass analyzer. The presence of cortisol in an artificial saliva sample was determined by the presence of 363 m / z, 385 m / z, 725 m / z and 747 m / z ions characteristic of the cortisol molecule. The comparison of the spectral profiles of saliva and saliva with cortisol showed the existence of spectral bands present in the cortisol spectrum that do not overlap with the saliva spectra, suggesting the monitoring of these regions to determine the concentration of cortisol in saliva samples. The principal component analysis (PCA) showed the formation of groups of samples, differentiating them in relation to the levels of cortisol concentration, proposing the methodology as a qualitative analysis of salivary cortisol levels. Finally, the analysis of the PCA loadings graph together with the attribution of the mass load ratios suggest the ions 363 m / z, 385 m / z and 747 m / z as markers to be used in a multiple linear adjustment in order to quantify the concentration of cortisol in saliva samples. The PS-MS technique proved to be efficient and promising for the real-time determination of salivary cortisol levels without using any sample preparation step. Starting from a volume of only 5.0 µL of sample, placed directly on the equipment's sampler, it was possible to obtain the identification by analyzing the mass spectrum in a time of approximately 45 seconds.
Keywords: Diagnóstico; Biofluidos; Método rápido; Cortisol; Engenharia Biomédica (Bioengenharia)